Increasing Knowledge, Skills, and Confidence Concerning Students’ Suicidality Through a Gatekeeper Workshop for School Staff - Brown, Rebecca C.; Straub, Joana; Bohnacker, Isabelle; Plener, Paul L. (Frontiers in Psychology, 2018)
Introduction: Around one third of adolescents in Germany report a lifetime history of suicide ideation. School staff (e.g. teachers or school social workers) can serve as gatekeepers to identify adolescents at risk and transfer them to appropriate mental health professionals. Aim of this study was to evaluate a gatekeeper training for school staff. Methods: A total of N=603 school social workers, school psychologists, and teachers participated in one of 33 1.5-day workshops. Knowledge, attitudes, confidence in skills, and perceived knowledge were assessed at pre and post workshops, and at six-month follow-up. Behavioral changes were assessed via self-report at follow-up. Results: Knowledge, perceived knowledge and confidence in own skills concerning suicidality increased significantly from pre- to post-assessment and was still significantly increased at six-month follow-up. Attitudes towards suicidal adolescents were neutral to positive before the workshop and remained un-changed at follow-up. Overall, participants were very satisfied with the workshop. Although participants stated to be motivated to make behavioral changes at six-month follow-up, they reported obstacles such as lack of resources and support from school-administration. Discussion: This 1.5-day gatekeeper workshop was effective in enhancing knowledge and confidence in school staff regarding suicidality. Future workshops would benefit from ongoing supervision and inclusion of school-administration in order to facilitate long-term changes on a behavioral level.